Pengaruh Good Corporate Governance dan Ukuran Perusahaan terhadap Nilai Perusahaan Perbankan yang Terdaftar di BEI Tahun 2021-2024 - Flora Aguilera; Usnia Wati Keristin (Universitas Multi Data Palembang, 2026)
This study aims to examine and analyze the influence of Good Corporate Governance and Company Size on firm value. The study employed a qualitative approach using secondary data sourced from companies' annual financial reports. The research subjects included the financial reports of banking companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The sample was selected using a purposive sampling technique, resulting in 37 research samples. Data analysis was conducted using descriptive analysis, multiple linear regression, classical assumption tests, t-tests, F-tests, and coefficients of determination. The research findings indicate that Good Corporate Governance has no effect on firm value, while firm size has been shown to influence firm value. However, both Good Corporate Governance and firm size simultaneously influence firm value.